HUBUNGAN ANTARA TINGKAT NYERI DENGAN KEMAMPUAN AKTIVITAS PADA PASIEN POST OPERASI SECTIO CAESAREA DENGAN ANESTESI SPINAL - Muhammad Yusuf; Suryanto Suryanto; Kaslinda Nur Umifa; Amin Zakaria (Institut Teknologi, Sains, dan Kesehatan RS.DR. Soepraoen Kesdam V/BRW, 2024)
Background: Post-operative caesarean section pain will cause limited mobilization due to the intensity of the pain. Significant pain can make it difficult for a person to move freely and carry out activities that require the use of the abdominal and pelvic muscles. This study aims to analyze the relationship between pain levels and activity ability in post-caesarean section surgery patients with spinal anesthesia. Method: This type of research is correlation analysis with a cross-sectional design on the patient population in the recovery room unit 24 hours after surgery, sampling quota with 30 respondents. The independent variable is the level of pain and the dependent variable is the ability to carry out activities. Pain levels were measured using a numeric rating scale pain scale observation sheet, ratio data scale. The ability to carry out activities is measured using an observation sheet, namely the ability to sit, stand and walk. Data analysis used the Pearson correlation test, using a computer aided by the SPSS 22 application. Results: There is a relationship between the level of pain and the activity ability of post-SC surgery patients with spinal anesthesia. The relationship is negative, namely the higher the level of pain, the lower the activity capacity. The level of relationship is very strong, namely -0.886. Conclusion: To be able to carry out walking activities, there would be at least moderate pain. The patient's advice is to reduce the level of pain to moderate and light levels so that they are able to carry out walking activities. Keywords: Pain, Activity Ability, Spindal Anesthesia, Sectio Caesarea